Activated Bone Marrow-Derived Macrophages Eradicate Alzheimer's-Related Aβ42 Oligomers and Protect Synapses - Li, Songlin; Hayden, Eric Y.; Garcia, Veronica J.; Fuchs, Dieu-Trang; Sheyn, Julia; Daley, David A.; Rentsendorj, Altan; Torbati, Tania; Black, Keith L.; Rutishauser, Ueli; Teplow, David B.; Koronyo, Yosef; et al. (Frontiers in Immunology, 2020)
Impaired synaptic integrity and function due to accumulation of amyloid β-protein (Aβ42) oligomers is thought to be a major contributor to cognitive decline in Alzheimer's disease (AD). However, the exact role of Aβ42 oligomers in synaptotoxicity and the ability of peripheral innate immune cells to rescue synapses remain poorly understood due to the metastable nature of oligomers. Here, we utilized photo-induced cross-linking to stabilize pure oligomers and study their effects versus fibrils on synapses and protection by Aβ-phagocytic macrophages. We found that cortical neurons were more susceptible to Aβ42 oligomers than fibrils, triggering additional neuritic arborization retraction, functional alterations (hyperactivity and spike waveform), and loss of VGluT1- and PSD95-excitatory synapses. Co-culturing neurons with bone marrow-derived macrophages protected synapses against Aβ42 fibrils; moreover, immune activation with glatiramer acetate (GA) conferred further protection against oligomers. Mechanisms involved increased Aβ42 removal by macrophages, amplified by GA stimulation: fibrils were largely cleared through intracellular CD36/EEA1+-early endosomal proteolysis, while oligomers were primarily removed via extracellular/MMP-9 enzymatic degradation. In vivo studies in GA-immunized or CD115+-monocyte-grafted APPSWE/PS1ΔE9-transgenic mice followed by pre- and postsynaptic analyses of entorhinal cortex and hippocampal substructures corroborated our in vitro findings of macrophage-mediated synaptic preservation. Together, our data demonstrate that activated macrophages effectively clear Aβ42 oligomers and rescue VGluT1/PSD95 synapses, providing rationale for harnessing macrophages to treat AD.